STRATEGI KOMUNIKASI PARIWISATA BERBASIS MASYARAKAT SEBAGAI UPAYA PENGEMBANGAN OBJEK WISATA BUDAYA DI DESA KOTO SENTAJO - Amelia Sukma Dewi; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This Community Based Tourism (CBT)-based tourism communication strategy involves local communities in the process of developing and promoting cultural tourism objects in Koto Sentajo Village. Local communities have an active role in tourism development. The local community uses a strategy by involving stakeholders in the development of cultural tourism objects in the village of Koto Sentajo, namely the government, academics, business actors, and the community and the media. Each stakeholder has its own role in tourism development. This study aims to find out how the community-based tourism communication strategy in developing cultural tourism objects in Koto Sentajo Village. This study uses a qualitative descriptive method. The determination of informants using purposive techniques. So that 10 informants were found. The data collection techniques in this study are observation, documentation, and interviews. While the technique of checking the validity of the data in this study is the technique of triangulation and member check. The data obtained were analyzed by reducing the data, presenting the data and drawing conclusions. The results of this study indicate that a community-based tourism communication strategy in developing cultural tourism objects in the village of Koto Sentajo can provide benefits to the village and can increase income in the village. The strategy carried out by the local community will later help in the welfare of the community and provide opportunities for local people in job opportunities. This community based tourism can provide opportunities for local communities in developing tourism where the local community will directly manage the tourism with the help of stakeholders who have helped Koto Sentajo Village to become a tourist village. The community and village government develop a communication strategy with five stakeholders, namely the government, universities, business people, the community and the mass media. The communication strategy developed by the community and village administration and stakeholders consists of planning, management and evaluation. In this communication strategy, stakeholders who assist in the development of the Koto Sentajo Tourism Village have their respective roles. Community strategies in establishing relationships with stakeholders will later have an effect on increasing tourists and tourism development. Through this community-based tourism strategy, the development of the Koto Sentajo cultural tourism object is running smoothly.